STUDY OF THE INFLUENCE OF CUSTOMER SATISFACTION ON WILLINGNESS TO PAY AND CUSTOMER LOYALTY AS MEDIATING VARIABLE (A Case Study towards Samsung Smartphone in Pontianak) - LIMAS B12111001, MONICA APRIYANA (Jurnal Manajemen Update, 2015)
Customer satisfaction and customer loyalty are important parts of a business which should be maintained by company to keep their existence in market. Company should observe and evaluate market condition frequently because customer needs and wants are changing along with the development of technology. Customer expectation toward certain product or services is one of customer satisfaction indicator and satisfaction has effect on customer loyalty which determines whether customer will repurchase the same product or not. This paper aims to examine customer satisfaction influence on customer loyalty and willingness to pay. The research used quantitative analysis research with Samsung Smartphone in Pontianak as the research object and used the sample of 100 respondents in Pontianak by using questionnaire to collect the data.Â  Collected data were analyzed with path analysis by using SPSS 16.0. The result analysis shows that all the hypotheses have positive and significant influence. Customer satisfaction has positive and significant influence towards customer loyalty and willingness to pay and customer loyalty has positive and significant influence toward willingness to pay. There are two hypotheses with contribution more than 50% which are customer satisfaction influence loyalty and loyalty influence willingness to pay. The influence of customer satisfaction on willingness to pay is only contributing 33.9%. The influence of customer satisfaction on willingness to pay through customer loyalty resulted insignificant influence with contribution only 0.072%. This means customer satisfaction direct influence on willingness to pay is better than the indirect influence. Â  Keywords: customer satisfaction, customer loyalty, willingness to pay more